The Effect of Standard Operating Procedures (SOPs), Supervision, and Information Technology on Employee Performance at JNE Outbound Unit Medan Main Branch - Ikwan Lubis; A.M Hatuaon Sihite; Maringan Sianturi; Nurin Natiqoh Lubis (Journal of Economics, Management and Accounting (JEMA), 2023)
JNE is the largest logistics company in Indonesia, this company is a freight forwarding service company both domestically and abroad. In the business process, JNE has an Outbound unit that is responsible for receiving goods from Sales Counter Official (SCO) agents and branch offices, processing, checking, packaging, and transporting goods to the appropriate destination. The purpose of this study is to determine the influence of Standard Operating Procedures (SOPs), supervision, and Information Technology on Employee Performance in the operational management of the JNE Outbound unit of the Medan Main Branch. This study uses the Descriptive Qualitative method in identifying problems. The results in this study state that SOPs have a significant effect on Employee Performance because they are an important part of the smooth work process for employees, Supervision and Information Technology also have a significant effect on Employee Performance. Supervision ensures that employees work in accordance with SOPs and achieve previously set work targets, and the use of Information Technology in the work process will increase the efficiency and effectiveness of work.